Variation in Onset of Leaf Unfolding and Wood Formation in a Central African Tropical Tree Species - Angoboy Ilondea, Bhely; Beeckman, Hans; Van Acker, Joris; Van den Bulcke, Jan; Fayolle, Adeline; Couralet, Camille; Hubau, Wannes; Kafuti, Chadrack; Rousseau, Mélissa; Kaka di-Makwala, Alain; Bourland, Nils; Deklerck, Victor; et al. (Frontiers in Forests and Global Change, 2021)
A diversity of phenological strategies has been reported for tropical tree species. Defoliation and seasonal dormancy of cambial activity inform us on how trees cope with water stress during the dry season, or maximize the use of resources during the rainy season. Here, we study the matching between leaf phenology (unfolding and drop) and cambial activity for Prioria balsamifera, a key timber species in the Democratic Republic of Congo. In particular, we (i) evaluated the seasonality of cambial activity and synchrony of phenology among trees in response to climate and (ii) identified the seasonality of leaf phenology and its relation with cambial phenology. The study was conducted in the Luki Man and Biosphere Reserve, located in the Mayombe forest at the southern margin of the Congo Basin. Historic defoliation data were collected every ten days using weekly crown observations whereas recent observations involved time-lapse cameras. Cambial pinning was performed on ten trees during 20 months and radius dendrometers were installed on three trees during 13 months. Tree rings were measured on cores from 13 trees and growth synchrony was evaluated. We found that P. balsamifera defoliates annually with a peak observed at the end of the dry season and the beginning of the rainy season. The new leaves unfolded shortly after shedding of the old leaves. The peak defoliation dates varied across years from 12 September to 14 November and the fraction of number of trees that defoliated at a given time was found to be negatively correlated with annual rainfall and temperature; during the dry season when precipitation and temperatures are the lowest. Wood formation (radial growth), was found to be highly seasonal, with cambial dormancy occurring during the dry season and growth starting at the beginning of the rainy season. Individual ring-width series don’t cross date well. The within species variability of leaf phenology and cambial rhythms provides information on resistance of the population against climate changes.